2015
DOI: 10.18632/oncotarget.5959
|View full text |Cite
|
Sign up to set email alerts
|

S-1 plus cisplatin versus fluorouracil plus cisplatin in advanced gastric or gastro-esophageal junction adenocarcinoma patients: a pilot study

Abstract: The safety and efficacy of S-1 plus cisplatin in Chinese advanced gastric cancer patients in first line setting is unknown. In this pilot study, patients with advanced gastric or gastro-esophageal junction adenocarcinoma were enrolled and randomly assigned in a 1:1 ratio to receive S-1 plus cisplatin (CS group) or 5-FU plus cisplatin (CF group). The primary endpoint was time to progression (TTP). Secondary end points included overall survival (OS) and safety. This study was registered on ClinicalTrials. Gov, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 21 publications
0
18
1
Order By: Relevance
“…GC is still the second most common cause of cancer‐related death in developing countries 3, 4, 5, 6, 7, 8, 9, 10. The estimated new GC patients in United States in 2017 are 28 000 and estimated deaths are 10 960 11.…”
Section: Introductionmentioning
confidence: 99%
“…GC is still the second most common cause of cancer‐related death in developing countries 3, 4, 5, 6, 7, 8, 9, 10. The estimated new GC patients in United States in 2017 are 28 000 and estimated deaths are 10 960 11.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies indicated that S-1 demonstrates far superior anti-tumor activities than 5-Fu and enhances the sensitivity of cancer cells to the effects of RT [10, 11]. Accumulating clinical evidence also supports the opinion that the combination of CDDP and S-1(CS) represents a viable treatment regimen for esophageal cancer [12, 13]. In studies performed in Japan, the CS regimen combined with RT in the setting of CCRT achieved encouraging response rates of 64.4%-–89.7%.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent trials have indicated that S-1 is effective against esophageal carcinoma and well-tolerated. Currently, there are five ongoing clinical trials that are evaluating its efficacy in various stages of disease and various esophageal cancer patients (17,18). Notably, one of these studies (NCT02347904) will test the feasibility of administering 6 cycles of oxaliplatin and S-1 as adjuvant therapy starting 12 weeks after esophagectomy.…”
Section: Future Directions In Systemic Therapymentioning
confidence: 99%